The Formalisation of Women's Cooperatives and the Reduct ion of the Informal Economy in Jordan, Fact or Fict ion? - Herenia Gutiérrez; Julián Chamizo González; Manar Moffadi Al-Mohareb (Revista de Economía Mundial, 2022)
This study examines the possible influence of formalising women's cooperatives on Jordan's informal economy. At the same time, to produce empirical evidence from a theoretical perspective, we study how the crucial challenges of the informal economy affect formalisation. This is an empirical study, both descriptive and inferential, in which several databases are used to extract the relevant data from the sample of 66 Jordanian women's cooperatives in the period from 2011 to 2020. A dynamic panel data model is used for the study variables with controlling for specific fixed effects. The findings indicate that the formalisation policy in the cooperative sector does not affect the informal economy. Instead, the challenges significantly affect the informal economy.